2000
DOI: 10.1177/095632020001100301
|View full text |Cite
|
Sign up to set email alerts
|

The Enantioselectivity of Enzymes Involved in Current Antiviral Therapy Using Nucleoside Analogues: A New Strategy?

Abstract: This review is primarily intended for synthetic bio-organic chemists and enzymologists who are interested in new strategies in the design of virus inhibitors. It is an attempt to assess the importance of the enzymatic properties of L-nucleosides and their analogues, particularly those that are active against viruses such as human immunodeficiency virus (HIV), hepatitis B virus (HBV), herpes simplex virus (HSV), etc. Only data obtained with purified enzymes have been considered and discussed. The examined enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 144 publications
0
19
0
Order By: Relevance
“…both L-dT and L-dC are efficiently phosphorylated. Several other L-nucleosides such as L-BVDU, L-FMAU (2¢-fluoro-5-methyl-b-L-arabinofuranosyluracil) and L-5-iodo-dU were also substrates for TK2 [78,82,88,92]. The role of TK2 in mtDNA synthesis was recently clarified since it was shown that two substitutions (Ile181 to Asn and His90 to Asn) in the TK2 gene lead to partial enzyme deficiency and to mtDNA depletion myopath [14].…”
Section: Mitochondrial Thymidine Kinasementioning
confidence: 99%
“…both L-dT and L-dC are efficiently phosphorylated. Several other L-nucleosides such as L-BVDU, L-FMAU (2¢-fluoro-5-methyl-b-L-arabinofuranosyluracil) and L-5-iodo-dU were also substrates for TK2 [78,82,88,92]. The role of TK2 in mtDNA synthesis was recently clarified since it was shown that two substitutions (Ile181 to Asn and His90 to Asn) in the TK2 gene lead to partial enzyme deficiency and to mtDNA depletion myopath [14].…”
Section: Mitochondrial Thymidine Kinasementioning
confidence: 99%
“…The structures of compounds described in Table (2). activate FIAU may be a contributing factor for the severe mitochondrial toxicity observed following treatment with this analogue [47]. Unexpectedly, the L-enantiomer of FMAU was found to be a relatively good substrate both for TK1 and TK2 (Table 1) [48], thus being the only reported Lnucleoside with TK1 substrate characteristics [49]. In contrast to TK1, both TK2 and HSV1-TK show relaxed enantioselectivity since they efficiently phosphorylate L-Thd as well as other L-nucleosides, such as L-BVDU, L-FMAU, and L-5-iodo-dUrd (26, 27, The elevated expression levels of TK1 in rapidly proliferating tumors, in contrast to quiescent cells, encouraged the synthesis of boronated nucleoside for boron neutron capture therapy (BNCT) [52].…”
Section: Substrate Activity Relationships Of Tk1 Tk2 Dm-dnk and Hsvmentioning
confidence: 99%
“…[3] In vivo, activation of L-nucleosides necessitates phosphorylation to the triphosphate. [4] While the first phosphorylation step has been extensively studied, less attention has been drawn to the second step. [4] This step, i.e., the phosphorylation of nucleosides monophosphate and their analogues into their diphosphate derivatives, involves nucleoside monophosphate kinases in both the de novo and salvage pathways.…”
Section: Introductionmentioning
confidence: 99%
“…[4] While the first phosphorylation step has been extensively studied, less attention has been drawn to the second step. [4] This step, i.e., the phosphorylation of nucleosides monophosphate and their analogues into their diphosphate derivatives, involves nucleoside monophosphate kinases in both the de novo and salvage pathways. [4,5] Human cells contain a thymidylate kinase (TMPK) and a uridine monophosphatecytidine monophosphate kinase (UMP-CMPK) that are only 21% identical in sequence but that adopt the same fold characterised by a P loop, a NMP binding domain and a LID domain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation